2007
DOI: 10.3354/cr00718
|View full text |Cite
|
Sign up to set email alerts
|

Linking fluctuations in rainfall to nonbreeding season performance in a long-distance migratory bird, Setophaga ruticilla

Abstract: Research on long-distance migratory birds has yielded some of the strongest evidence that shifts in climate are changing ecosystem processes. Much of this work has focused on understanding whether rising temperatures on temperate breeding grounds are advancing migration phenology and limiting reproductive success. However, conditions on tropical nonbreeding quarters can also shape these processes, yet few studies have directly measured bird responses to climate during this part of the annual cycle. We tested t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
218
3
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(238 citation statements)
references
References 52 publications
(59 reference statements)
13
218
3
4
Order By: Relevance
“…Although we have not measured this threshold directly, carrying capacity is probably related to the availability of arthropod prey. We previously found that dry season rainfall predicted food availability in both mangrove and scrub habitat [38,41]. Our finding that conspecific density explained more variation in body condition than rainfall suggests that the potential benefits of elevated food were more often accompanied by intense competition for resources.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Although we have not measured this threshold directly, carrying capacity is probably related to the availability of arthropod prey. We previously found that dry season rainfall predicted food availability in both mangrove and scrub habitat [38,41]. Our finding that conspecific density explained more variation in body condition than rainfall suggests that the potential benefits of elevated food were more often accompanied by intense competition for resources.…”
Section: Discussionmentioning
confidence: 62%
“…We analysed only birds captured in spring (15 March-15 April). Body condition at this time of year reflected environmental conditions across the non-breeding period [36,38]. We estimated body condition as the standardized residuals from a regression of body mass on tarsus and wing length.…”
Section: (C) Statistical Analysesmentioning
confidence: 99%
“…Marra and Holberton, 1998;Marra and Holmes, 2001;Latta and Faaborg, 2002;Brown and Sherry, 2006;Studds and Marra, 2007;Smith et al, 2010) and the timing of migration Studds and Marra, 2005;Gunnarsson et al, 2006;Bridge et al, 2010). This can ultimately lead to carry-over effects on breeding success Reudink et al, 2009;Inger et al, 2010), survival (Johnson et al, 2006;Angelier et al, 2009) and natal dispersal (Studds et al, 2008), such that non-breeding and breeding life history stages interact across geographical space.…”
Section: Introductionmentioning
confidence: 99%
“…The observed change in arrival date in long-distance migrants may be at variance with the notion of rather inflexible timing mechanisms described above, but these changes may be the result of improved conditions en route, allowing faster migration rather than an earlier onset of migration (Huin & Sparks 1998, Coppack & Both 2002, Ahola et al 2004, Bairlein & H眉ppop 2004, Both et al 2005, Gordo & Sanz 2005, H眉ppop & Winkel 2006, Gordo 2007. Migration dates may also change because of changed conditions at the wintering grounds, allowing birds to start migration earlier (Cotton 2003, Saino et al 2004, 2007, this issue, Sparks & Tryjanowksi 2007, Studds & Marra 2007, although these circumstances may be unrelated to phenological conditions at the breeding grounds.…”
Section: Introductionmentioning
confidence: 99%